Impacto econômico do Programa BR do Mar: uma análise de equilíbrio geral por meio do PAEG - TLOG - Barbosa, Márcio Nora (Universidade do Vale do Rio dos Sinos, 2022)
The aim of this dissertation is to investigate the relationship of the national transportation infrastructure, specially the ports, with the domestic and external Brazilian trade, analyzing the possible effects that the Brazilian government policy to encourage the cabotage (“Br do Mar” program) could exert on the country’s cargo transportation matrix and interregional routes, as well as verify the effects on the national economic sectors and the spillover effects on Brazil's international trade. To reach this aim, a Computable General Equilibrium Model, called PAEG-TLOG was developed, based on the GTAP model version 10. This model presents the interregional transport matrix and its respective routes in 4 different modes of transport. The results indicate that the “BR do Mar” program generates a greater balance in the interregional transport matrix, with a greater participation of cabotage, due to market gains over the road modal, representing a reduction of approximately 410 thousand trucks on the long distances roads, reducing accidents, theft and damage costs and generating lower levels of pollution. The sectorial effects indicate that the productive sectors located in the Northeast, Southeast and North regions have greater increases in production levels (mostly), with emphasis on the Rice and Chemical sectors. However, the Soybean sector and the transport services sector presented losses in productive activity. The aggregate effects generate an increase in Brazilian GDP and welfare of around 0.1% for both variables. The foreign trade showed to be the GDP component that most contributes to this positive balance, with increases in exports of 0.09% and 0.06% for imports. The results corroborate with the scenario that a more balanced transport matrix reduces the production and marketing costs, making the regions more competitive, increasing their consumption and production, and enabling a greater participation in international trade due to the greater competitiveness of their products.
Keywords: Infraestrutura de transporte; Cabotagem; Programa BR do Mar; Equilíbrio geral computável; PAEG-TLOG; Transport infrastructure; Cabotage; BR do Mar Program; Computable General Equilibrium; ACCNPQ::Ciências Sociais Aplicadas::Economia